Further Discoveries of Cross-Slabs in the Isle of Man - Kermode, P (Proceedings of the Society of Antiquaries of Scotland, 1916)
A report on the discovery of nine more pieces, including two very small and imperfect fragments, making a total of twenty-six brought to light since the publication of Manx Crosses in 1907. Each is described and illustrated in detail. A late cross with runic inscriptions, a Viking ship and part of a Celtic cross is particularly noteworthy.